The Role of Forensic Accountants In Fraud Disclosure In Indonesia - Salza Adzri Arismutia (JAF (Journal of Accounting and Finance), 2022)
This research is designed to employ qualitative research method with the Association of Certified Fraud Examiners as data source. The data is collected using documentation technique, which means the data comes from the books that have discussed the duties and responsibilities of a forensic accountant. Forensic accounting is a development of accounting disciplines that is still relatively new. The current availability of the profession is less than 10%, and has very good prospects in the future. This is what motivates the author to introduce and explain to readers, especially accounting graduates, about the expansion of the new profession from the development of accounting science. The fraud which frequently happens in state-owned institutions is the reason for the emergence of forensic accounting profession in Indonesia. Fraud itself is one of the problems that continues to occur until now. There is no institution or company institution that can really be free from fraud possibility. Fraud perpetrators are also present at all levels, both in the upper and lower classes of employees. Eradication of fraud in corruption is an opportunity as well as a challenge for them.